Performance and carcass quality in comercial lines of broilers - de Avila, Valdir Silveira; Ledur, Mônica Corrêa; Junior, Waldomiro Barioni; Schmidt, Gilberto Silber; Costa, Claudio Napolis (Pesquisa Agropecuaria Brasileira, 1993)
Four commercial lines of broilers (AA, PL, CB and HB) were evaluated in order to compare their performance, and carcass yield and composition. The experiment was divided into three groups: males (M), females (F) and mixed (M+F). Feed intake (CR), body weight (PC), feed conversion (CA) and viability (VB) up to 49 days were measured using a pen as the experi-mental unit. At 50 days of age, one bird was removed at random from each pen in the M and F groups and one male and one female from each pen in the M + F groups, in order to evaluate car-cass yield (RC), percentage of abdominal fat relative to live weight (PGA) and to eviscerated car-cass weight (PCE). Significant differences (P < 0.05) were observed between lines in relation to CA, with best results for line PL. In relation to carcass traits, CB birds showed the lowest PC and AA birds the lowest RC. The effect of groups was significant (P < 0.05) for all traits except for VB. Females presented lower PV, PC and RC and higher PGA and PCE than males. Significant phenotypic correlations were observed between PV and PC (r = 0.98), PCE and RC (r = 0.52) and PV and RC (r = 0.35). Similar results were observed when the line was taken into conside-ration, except for HB birds, for which the correlation between PV and RC was not important.